Pengembangan Media Pembelajaran Kosakata Bahasa Arab Berbasis Android - Wijayanti, Hani Nurlaeli; Warseto, Andri (Department of Arabic Teaching, STAI PUI Majalengka, 2025)
The development of mobile learning technology has opened new opportunities in the learning process, including Arabic language learning. One of the most popular platforms in Indonesia is Android, which is open source and easily accessible to various groups. MAN 1 Banjarnegara, as an educational institution under the Ministry of Religious Affairs, designates Arabic as a compulsory subject. However, preliminary studies indicate low student interest—particularly among tenth-grade students—in learning Arabic due to limited classroom time, lack of a language-rich environment, and the perception that the subject is difficult. To address this issue, this study develops an Android-based Arabic vocabulary (mufrodat) learning medium integrated into classroom activities. This medium is designed to help students understand vocabulary, improve reading skills, and increase interest in learning Arabic. The focus of the study is on tenth-grade religious studies students at MAN 1 Banjarnegara in the 2015/2016 academic year. It is expected that this medium will serve as an innovative solution applicable not only at the Madrasah Aliyah level but also across other educational levels.